Overview of Physical and Pharmacological Therapy in Enhancing Bone Regeneration Formation During Distraction Osteogenesis - Liu, Ze; Liu, Qi; Guo, Hongbin; Liang, Jieyu; Zhang, Yi (Frontiers in Cell and Developmental Biology, 2022)
Distraction osteogenesis (DO) is a kind of bone regeneration technology. The principle is to incise the cortical bone and apply continuous and stable distraction force to the fractured end of the cortical bone, thereby promoting the proliferation of osteoblastic cells in the tension microenvironment and stimulating new bone formation. However, the long consolidation course of DO presumably lead to several complications such as infection, fracture, scar formation, delayed union and malunion. Therefore, it is of clinical significance to reduce the long treatment duration. The current treatment strategy to promote osteogenesis in DO includes gene, growth factor, stem-cell, physical and pharmacological therapies. Among these methods, pharmacological and physical therapies are considered as safe, economical, convenience and effective. Recently, several physical and pharmacological therapies have been demonstrated with a decent ability to enhance bone regeneration during DO. In this review, we have comprehensively summarized the latest evidence for physical (Photonic, Waves, Gas, Mechanical, Electrical and Electromagnetic stimulation) and pharmacological (Bisphosphonates, Hormone, Metal compounds, Biologics, Chinese medicine, etc) therapies in DO. These evidences will bring novel and significant information for the bone healing during DO in the future.